Implementation of rational choice theory to the analysis of events in Ukraine 2013-2016 - Tetiana Kalenychenko (Cхід, 2016)
The theory of rational choice of religion became one of the leading for scientific world, by total changing paradigm of postsecular sociology of religion. But its critics does not give to us any possibility apply it fully to non-american societies, and also analyze the impact of social factors on perception of religion personally and by collective. The problem is taking into account many other factors that also have a place in modern forms of conflict. Consideration of this theory in a context of latest events in Ukraine 2013-2016 gives us possibility to look on perspectives of its implementation. A more detailed analysis shows the lack of a theory to explain the multifaceted conflict that is present in Ukraine, what means that researcher need more theoretical background to explain new phenomena. The presence of religious component in a social and political conflict creates more difficult conditions for in-depth analysis and finding root causes of primary conflict. Still theory of rational choice of religion explains part of the trends that emerged two years ago and continue to develop in the Ukrainian society. Since the first revolution and later open armed conflict led to the transition of society in another dimension, placing new challenges and tasks, but bared old problems and latent conflicts, especially in religious organizations and groups.